Increasing the Value of Aquaculture Fish Products through Processing to Become Sambelingkung in Lubuk Factory Village - Nuraini; Bina Aulia Zafana; Erida Kanalia; Gita Tamara; Habib Fadhilah; Maessy Pradella; Nia Nopita Sari; Adi; Yuandita Sepgianti; Zikri Aprillah Pratama; Nurzaidah Putri Dalimunthe (PT FORMOSA CENDEKIA GLOBAL, 2023)
This activity aims to increase the value of cultivated fish products into sambelingkung so that it becomes the latest innovation for managers. The implementation of this activity starts from observing fish ponds, processing sambelingkung products, marketing strategies and product counseling activities. The result of this activity is the creation of an innovative product from pond fish, so that fish products from ponds are not only sold in the same way continuously but there are innovations such as being processed into complementary foods, namely sambelingkung. This activity is very useful in increasing the knowledge, insight and skills of managers, PKK and KWT mothers. In addition, further innovation is needed in order to get better results and quality. And this is the result of fish ponds having new businesses apart from existing ones to increase and maximize the profit on the selling price of catfish.